Experiences of mothers of children with severe intellectual disability regarding partner support in the Capricorn District, Limpopo Province - Makgoga, Malope Tshegofatjo (My University, 2023)
Background: Raising a child with a severe intellectual disability is a challenge for most mothers, as most mothers experience a lack of support from their partners. This lack of partner support causes high stress and marital problems for mothers. Purpose: The purpose of the study was to determine the experiences of mothers of children with a severe intellectual disability regarding partner support in the Capricorn District, Limpopo Province. Study method: A qualitative, explorative, and descriptive design was applied to explore and describe the experiences of mothers of children with a severe intellectual disability regarding partner support. Participants were selected using a purposive sampling method. Data were collected from twelve mothers of children with severe intellectual disability using a semi-structured interview guide. Data were analysed using Tesch’s approach to data analysis. Trustworthiness was ensured by using four criteria of trustworthiness, credibility, dependability, confirmability, and transferability. Ethical clearance was obtained from the Turfloop Research Ethics Committee (TREC) and permission to collect data was granted by the Department of Education Limpopo Province and the principals of the selected special schools. The details of the study were explained to the participants who then agreed to participate in the study by signing a consent form. Results: The findings of the study showed that mothers experienced negative and positive partner support. The positive supports include caring about and loving the child, having a positive relationship with the child, and having instrumental support through sharing supervision and caring. The most negative support was partners not accepting the child, partners lacking emotional support and marital relationship challenges. Limitation: Data was collected during the COVID-19 lockdown, which delayed getting permission to collect data as the schools were closed for a long time. Conclusion: The healthcare practitioners as the first people to identify the disability, should immediately inform the mothers and their partners about the child’s disability and start with counselling immediately and continue with counselling throughout the development. The recommendation of the study focused on the promotion of partner support through research, education and training
Thesis (M.A. (Nursing) -- University of Limpopo, 2023
Keywords: Experiences; Mothers; Children; Severe intellectual disability; Partner; Support; Mothers of children with disabilities; Intellectual disability; Developmental psychology